1998
DOI: 10.1007/bf02235758
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusions reduce long-term survival following surgery for colorectal cancer

Abstract: We found an independent and significant association between perioperative blood transfusion and poor prognosis in colorectal cancer patients. Blood storage time was not a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 42 publications
4
49
0
2
Order By: Relevance
“…This angiogenic factor imbalance was associated with enhanced in vitro angiogenesis. However, Edna and Bjerkeset [6] failed to find any relationship between the time of blood storage and long-term prognosis. On the other hand, Mynster et al [20] showed that buffy-coat-depleted red cells stored for less than 21 day could be an independent risk factor for cancer recurrence, while blood stored more than 21 days had insignificant effect on the risk of recurrence.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This angiogenic factor imbalance was associated with enhanced in vitro angiogenesis. However, Edna and Bjerkeset [6] failed to find any relationship between the time of blood storage and long-term prognosis. On the other hand, Mynster et al [20] showed that buffy-coat-depleted red cells stored for less than 21 day could be an independent risk factor for cancer recurrence, while blood stored more than 21 days had insignificant effect on the risk of recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…Following these early reports, several other studies have been published in the literature with contradictory results. Some of these studies have shown an adverse effect of transfusion on the prognosis of patients with colorectal carcinoma [4][5][6]. Conversely, others have found no transfusion-dependent effect on survival and recurrence [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Patients given pre-operative oral iron supplements were discharged from hospital earlier than the non-intervention group (median length of stay 11.5 days [range, 6-35 days] in no-iron group, 10 days [range, 6-26 days] in the iron group; not significant). This may, in part, be secondary to the reduced level of transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were unexpected because a growing number of publications suggest that outcomes are unfavorable after transfusion of RBCs with prolonged storage age, [25][26][27][28] although there is by no means a consensus regarding the effect of blood storage age on cancer recurrence. 29,30 Gao et al 31 demonstrated the presence of circulating prostate cancer cells in the peripheral blood obtained from patients with prostate cancer immediately before prostatectomy. Therefore, the perioperative period is critical in the cancer disease process because any immunosuppressive intervention may facilitate formation of micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…17 The clinical evidence of the effect of blood storage age on cancer recurrence is less clear than the evidence in animal models. For example, Edna and Bjerkeset 29 found that blood storage time had no effect on local recurrences and distant metastases in 336 patients who had colorectal resective cancer surgery. However, Mynster and Nielsen 30 demonstrated that, compared with patients who did not undergo transfusion, those who received allogeneic blood stored for less than 21 days had increased locoregional cancer recurrence after colorectal surgery, whereas those who underwent transfusion with blood with a storage age older than 21 days had a recurrence rate similar to that of nontransfused patients.…”
Section: Discussionmentioning
confidence: 99%